The Effect Of Work Experience And Competence On Employee Performance Through Job Satisfaction Of PDAM Surya Sembada Employees In Surabaya City - Sumilat, Mario Revoldy; Osijo, Immanuel Ustradi; Sumunu, Trenggono; Soleha, Siti Nur; Zainuddin, Ahmad (Abadi Institute, 2025)
This study aims to analyze the influence of Work Experience and Competence on Employee Performance, either directly or through the mediation variables of Job Satisfaction in PDAM Surya Sembada Kota Surabaya. The research method uses a quantitative approach with census techniques or saturated sampling of the entire employee population, as many as 93 people. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through SmartPLS 3.0 software. The results of the study show that Work Experience and Competence have a positive and significant effect on Employee Performance, both directly and indirectly through Job Satisfaction. These findings indicate that improving employee work experience and competencies not only increases job satisfaction but also impacts overall performance improvement. Therefore, the development of competencies and work experience is an important strategy in efforts to improve organizational performance.